Research of the Ramp Start Control of Signal Speed Ratio Electric Vehicle - Zhang Qing; Xiong Huiyuan (Jixie chuandong)
For signal speed ratio electric vehicle is prone to slide backward under ramp start condition,a ramp start control strategy based on road gradient identification is proposed. The kinematics linear regression model of the signal speed ratio electric vehicle under ramp start condition is constructed,then a road gradient identifier based on multi-innovation forgetting gradient algorithm is designed,the ramp anti-slide control strategy is formulated according with driver intention. The system simulation model is built in Matlab / simulink,the results indicates that the ramp start control method could well indentify road gradient,the ramp slide backward phenomenon is effectively prevented and the vehicle start characteristic is improved.